Responses and reliability of candidate intensity measures to different mental and motor load levels of an upper limb exergame in children and adolescents with neurological diagnoses - Goikoetxea-Sotelo, Gaizka; van Hedel, Hubertus J. A. (Frontiers in Rehabilitation Sciences, 2025)
BackgroundHigh-intensity therapy improves outcomes in (pediatric) neurorehabilitation, yet standardized intensity measures accounting for motor and/or mental demands remain scarce.ObjectivesTo evaluate the responses and test-retest reliability of heart rate variability (HRV), skin conductance (SC), activity counts and movement repetitions normalized for the maximal capacity (%ACmax and %MOVmax, respectively), and the NASA-TLX across personalized motor and mental load levels in children and adolescents with neurological diagnoses using upper limb exergames.MethodsIn a cross-sectional study, participants engaged in two custom exergames at three intensity levels (“very easy,” “challenging,” “very difficult”), each lasting 3 min. Responses of the candidate intensity measures were analyzed across conditions, and intraclass correlation coefficients (ICC) assessed reliability across two consecutive sessions.Results30 children and adolescents with neurological diagnoses aged 9–19 years participated in the study. %MOVmax and NASA-TLX (overall, effort, mental) responded to both mental and motor intensity increases. HRV, %ACmax, and NASA-TLX physical subscale responded to motor load only. SC showed no consistent response. HRV and %ACmax demonstrated the highest reliability (ICC > 0.75), especially under motor conditions. NASA-TLX effort showed potential as a simplified surrogate for the full scale, though with variable reliability.ConclusionChanges in motor intensity were better captured than changes in mental intensity. Combining HRV, %ACmax, and NASA-TLX effort could offer a multidimensional approach to quantify therapy intensity. However, many measures lacked sufficient reliability or feasibility for clinical implementation. Further research is needed to validate these measures in real-world therapeutic settings and clarify their relationship to individual capacity.